2011
DOI: 10.1074/jbc.m111.262857
|View full text |Cite
|
Sign up to set email alerts
|

Occludin Localizes to Centrosomes and Modifies Mitotic Entry

Abstract: Proper control of cell cycle progression and barrier function are essential processes to the maintenance of epithelial cell homeostasis. The contribution of tight junction proteins to barrier function is well established, whereas their contribution to cell cycle control is only beginning to be understood. Centrosomes are the principal microtubule organizing centers in eukaryotic cells and centrosome duplication and separation are linked to the cell cycle and mitotic entry. Here we demonstrate that occludin loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 50 publications
7
34
0
Order By: Relevance
“…The present study demonstrates the necessity of size-reductive proliferation or cell packing for normal barrier maturation and identifies a role for the TJ protein occludin in this process. Previous studies demonstrated that occludin contributes to growth control and cell cycle progression (15,20), is altered in epithelial cancers (44,45), and may act as a tumor suppressor (20). Evidence is presented here demonstrating that the phosphorylation of S471 of occludin regulates entry into size-reductive proliferation after cell contact.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The present study demonstrates the necessity of size-reductive proliferation or cell packing for normal barrier maturation and identifies a role for the TJ protein occludin in this process. Previous studies demonstrated that occludin contributes to growth control and cell cycle progression (15,20), is altered in epithelial cancers (44,45), and may act as a tumor suppressor (20). Evidence is presented here demonstrating that the phosphorylation of S471 of occludin regulates entry into size-reductive proliferation after cell contact.…”
Section: Discussionmentioning
confidence: 69%
“…All reagents were purchased from Sigma Chemical (St. Louis, MO) unless otherwise noted. MDCK cells were obtained from the American Type Culture Collection (Manassas, VA) and cultured in minimum essential medium (MEM) as previously reported (15). All cells were kept at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The attack cemented support for Aideed, who was not at the house, and fueled outrage among the Somali people, in turn contributing to the carnage when Army Special Operations Forces tried to capture Aideed during the "Black Hawk Down" incident later that year. 284 Concerns about civilian casualties also resulted in the cancellation of several attempts to target bin Laden between 1997 and 1999, as discussed later.…”
Section: Obstacles To Hvt Operationsmentioning
confidence: 99%
“…Claudins (Furuse et al, 1998), (Furuse et al, 2002), (Nitta et al, 2003), (Turksen and Troy, 2002), (Tatum et al, 2010), (Nakano et al, 2009), (Gow et al, 1999), (Gow et al, 2004), (Ben-Yosef et al, 2003), (Tamura et al, 2008), (Simon et al, 1999), (Miyamoto et al, 2005), (Hou et al, 2009), (Angelow et al, 2008) Occludin (Furuse et al, 1993), (Traweger et al, 2002), (Sakakibara et al, 1997), (Saitou et al, 2000), (Furuse et al, 1998), (Du et al, 2010), (Runkle et al, 2011) MarvelD3 (Raleigh et al, 2010), (Steed et al, 2009) Tricellulin (Ikenouchi et al, 2005), (Ikenouchi et al, 2008) LSR (Masuda et al, 2011) JAMs (Hirabayashi and Hata, 2006), (Weber et al, 2007), (Kostrewa et al, 2001), (Laukoetter et al, 2007), (Pellegrini et al, 2011), (Ishida et al, 2003) …”
Section: Recommended Readingmentioning
confidence: 99%